Integrating Maternity Gymnastics and Effleurage Massage into Midwifery Care: A Complementary Strategy for Maternal Comfort and Efficient Labor - Mahmudah, Siti; Salsabia, Sabrina; Karuniawati, Benny (STIKep PPNI Jawa Barat, 2025)
Background: Maternal morbidity and mortality remain significant public health challenges in Indonesia. Complications such as labor pain, sleep disturbances, and fetal malposition continue to affect maternal outcomes. Complementary therapies, including maternity gymnastics and effleurage massage, have emerged as potential strategies to enhance maternal comfort and promote efficient labor. Objective: This study aimed to evaluate the effects of integrating maternity gymnastics and effleurage massage into midwifery care on improving maternal sleep quality, fetal descent, and labor outcomes. Methods: A quasi-experimental, one-group pretest-posttest design was employed. Forty-two pregnant women between 32 and 36 weeks gestation were recruited consecutively from a public health center in West Java, Indonesia. Participants engaged in weekly maternity gymnastics sessions and received effleurage massage during the first stage of labor. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), and labor outcomes were recorded using a validated checklist. Data were analyzed using paired t-tests and descriptive statistics. Results: There was a significant improvement in sleep quality following the intervention, with the mean PSQI score decreasing from 8.6 ± 2.1 to 5.2 ± 1.8 (p < 0.001). The mean duration of the first stage of labor was 4.3 ± 1.1 hours. A high proportion of participants achieved spontaneous vaginal delivery (90.5%), and early fetal head engagement at admission was observed in 83.3% of cases. Labor pain intensity was moderate, with a mean Visual Analog Scale (VAS) score of 5.7 ± 1.4. Conclusion: Integrating maternity gymnastics and effleurage massage into midwifery care effectively improved maternal sleep quality, facilitated fetal engagement, and promoted shorter labor duration. These findings support the incorporation of complementary therapies into routine antenatal and intrapartum care to enhance maternal comfort and optimize labor outcomes.